2019
DOI: 10.1016/j.euf.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Synthesis to Accelerate and Improve the Evaluation of Therapies for Metastatic Hormone-sensitive Prostate Cancer

Abstract: There are many ongoing randomised trials of promising therapies for metastatic hormone sensitive prostate cancer (mHSPC), but standard systematic reviews may not synthesise these in a timely or reliable way. We demonstrate how a novel approach to evidence synthesis is being used to speed up and improve treatment evaluations for mHSPC. This more prospective, dynamic and collaborative approach to systematic reviews of both trial results and individual participant data (IPD) is helping to establish quickly and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…An obvious limitation of all included reviews is their use of aggregate data. An individual participant data NMA is currently being conducted within the STOPCAP M1 programme [56,57], and should allow many of the issues discussed here to be resolved. As the majority of data were from large-scale randomised controlled trials, we did not attempt to draw any conclusions about the possible effects of trial-level bias on review results.…”
Section: Discussionmentioning
confidence: 99%
“…An obvious limitation of all included reviews is their use of aggregate data. An individual participant data NMA is currently being conducted within the STOPCAP M1 programme [56,57], and should allow many of the issues discussed here to be resolved. As the majority of data were from large-scale randomised controlled trials, we did not attempt to draw any conclusions about the possible effects of trial-level bias on review results.…”
Section: Discussionmentioning
confidence: 99%
“…Individual participant data (IPD) is generally seen as the "gold standard" [51], and would allow many of the issues discussed here to be resolved. No IPD review in this setting yet exists, but the STOPCAP M1 programme [52] aims to develop an IPD repository to allow this work to be done [53] and to allow other researchers to tackle new questions as they arise going forward.…”
Section: Discussionmentioning
confidence: 99%
“…Prospectively designed topic-based repositories take this approach a step further by mapping out the trial landscape, before most have completed and reported, to address a series of questions (both known and as yet unknown) within a specific topic area. One such example is the STOPCAP M1 repository of trials conducted in metastatic hormone-sensitive prostate cancer [ 24 ]. Using a prospective approach allows researchers to anticipate upcoming, clinically relevant, and important questions as the treatment paradigm evolves, and direct engagement with investigators facilitates the conduct of prospective meta-analyses of aggregate data that can guide the strategic collection of IPD [ 25 ].…”
Section: The Current Clinical Data Sharing Landscapementioning
confidence: 99%